Retrospective study of clinically relevant maxillary and mandibular anatomy in all skull types of dogs and cats - Schellenberg, Erinn; Lowe, Candace (Frontiers in Veterinary Science, 2025)
IntroductionIn this retrospective study, computed tomography (CT) imaging was used to examine skull types of cats and dogs to provide clinically useful information for improved patient safety, regarding ocular trauma and hemorrhage control during dental nerve block administration, extraction of the caudal maxillary teeth, and caudal maxillectomy or mandibulectomy.Materials and methodsCT imaging was used to examine the images of 193 dogs and 41 cats, which were divided into mesocephalic (≤5, 6–10, and ≥11 kg), brachycephalic (≤10 and ≥11 kg), dolichocephalic (≤10 and ≥11 kg) dogs, and mesocephalic and brachycephalic cats. Descriptive statistics were calculated for infraorbital canal length, width and height, shortest distances for infraorbital foramen to globe, maxillary foramen to globe, and maxillary first and second molar tooth root apex to globe in dogs, and apices of the maxillary fourth premolar tooth to globe in cats, palate to maxillary foramen, palate to globe, and mandibular molar to mandibular foramen in all cats and dogs. Values were tabulated and combined into reference materials to aid veterinarians in making safer clinical decisions.ResultsThe shortest maxillary molar tooth root apex-to-globe minimum value was 2.1mm in mesocephalic ≤5kg dogs. The shortest minimum palate-to-globe distance was 5.3mm in mesocephalic dogs of 6-10kg. The minimum maxillary fourth premolar tooth root apex-to-globe distances ranged from 1.6-2.8mm in all cats. Accidental globe puncture through the infraorbital canal was possible in 100% of cats and dolichocephalic ≤10kg dogs, and between 81-95% of mesocephalic dogs weighing 10kg or less.ConclusionCaution should be taken when performing infraorbital and maxillary nerve blocks in mesocephalic and dolichocephalic dogs ≤10 kg and all cats. Using proper technique, brachycephalic ≥11kg dogs may be at lower risk of accidental globe trauma during infraorbital nerve block. The deep maxillary nerve block should not be used in cats or small dogs. The maxillary nerve block, using the modified infraorbital canal approach, combined with the author’s recommended safe needle/catheter insertion distances should provide safe, effective analgesia administration. Mean measurements for mandibular molar to mandibular foramen, and maxillary molar to maxillary foramen may be used for surgical planning and ligation for hemostasis for caudal mandibulectomies and maxillectomies, particularly when CT imaging is not available.